Fatty acid composition and oil content during coriander fruit development. (1st October 2020) - Nguyen, Quang-Hung; Talou, Thierry; Evon, Philippe; Cerny, Muriel; Merah, Othmane
Highlights: Stressed conditions reduced oil and fatty acids accumulation in coriander fruits. Saturated and polyunsaturated fatty acids were predominant at earlier ripening stages. Petroselinic acid reached its higher level at twenty four days after flowering. Abstract: Coriander contains petroselinic acid, an isomer fatty acid of oleic acid. Coriander seed oil has been proposed as novel food ingredient in the European Union. Field experiments were performed at Auch (France) during two seasons (2010 and 2011). From flowering to maturity, fruits were harvested weekly and oil content and fatty acid (FA) compositions were determined. Fruits presented 2% more oil in 2010 than in 2011. Petroselinic acid (PA) contents was higher in 2011 than in 2010. Oil accumulation began earlier after flowering (2 DAF) in 2011. A first step in accumulation was identified between two and 21 DAF characterized by high SFA and PUFA, which decreased 21 DAF. Subsequently, PA increased to its highest concentration (30–55 DAF) and SFA and PUFA reached their lowest. These results suggest that higher concentrations of PA can be achieved by collecting fruits before full maturity.